2012
DOI: 10.4236/fns.2012.32030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactic Acid Bacteria and Yeast Starter Cultures on the Soaking Time and Quality of “Ofada” Rice

Abstract: Freshly harvested paddy rice was randomly obtained from three different farms in "Ofada" town, Ogun State, Nigeria and processed according to the traditional parboiling method. The rice was inoculated singly with cultures of Lactobacillus amylophilus, Leuconostoc mesenteroides, Saccharomyces uvarum and Saccharomyces cerevisiae which were isolated from the soak-water. In order to assess the effect of starter cultures on the soaking time of the rice, the pH and titratable acidity were determined at 12 h interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…Ash content of processed rice ranged from 0.24 to 0.71 with an average value of 0.515 %. Ash content reported in this work is lower than that obtained by Adeniran et al (2012) but within the range of that reported by Adekoyeni (2014) in a study of effect of storage and processing condition on Ofada rice quality.…”
Section: Proximate Composition Of Milled Ofada Ricesupporting
confidence: 86%
See 3 more Smart Citations
“…Ash content of processed rice ranged from 0.24 to 0.71 with an average value of 0.515 %. Ash content reported in this work is lower than that obtained by Adeniran et al (2012) but within the range of that reported by Adekoyeni (2014) in a study of effect of storage and processing condition on Ofada rice quality.…”
Section: Proximate Composition Of Milled Ofada Ricesupporting
confidence: 86%
“…As presented in This could be associated with variation in the drying temperature. Moisture content reported in this work is lower than that obtained by Adeniran et al (2012) but within the range of that reported by Anuonye et al (2016) who reported moisture content range of 8.24 to 10.21 g/100g. When sun drying was used by Fagbohun and Oluwaniyi (2015) in a study on milled rice storage, a range of 7.84 to 11.72 % was obtained for milled rice moisture content.…”
Section: Proximate Composition Of Milled Ofada Ricesupporting
confidence: 82%
See 2 more Smart Citations
“…Ofada town is noted for its unique rice‐processing technology that makes the product different from other types of rice. The processing of “Ofada” rice involves soaking the rice in water for 72 h (hydration), which confers a unique flavor on the rice that is relished by many people (Adeniran 2010), followed by steaming, drying and milling. The developed flavor is as a result of the fermentative activities of microorganisms during the soaking process, which affects the organoleptic, physical and nutritional composition of the soaked rice (Otegbayo et al .…”
Section: Introductionmentioning
confidence: 99%